A study on the current situation and development strategies of collegiate sports in China - Yang, D.; Lv, P. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Over the past 20 years, significant progress has been made in the Chinese collegiate sports which are the important part of the "whole-nation system" of sports. However, the pace of collegiate sports development has been slowing down recently as a result of many existing problems associated with collegiate sports. The purpose of this study was to analyze the sources of the problems and propose approaches to dealing with those problems. Methods In the present study, athletic administrators, coaches, and athletes from 25 collages in Beijing and five other administrative regions of the country were studied. In addition, relevant documents were reviewed and questionnaires were administered to participants. Results Several problems were identified as a result of the study. Firstly, the "Tsinghua model" is not popularized nor adopted by professionals in the field of physical education and sports across the nation. Secondly, the theory of "sports taught in conjunction and combination with education" needs be explained and discussed. Thirdly, the "student-athletes model" has not been realized and various "Students Leagues" have not been developed on college campuses. Finally, there is a strong need to put forward corresponding countermeasures for the sustainable development of collegiate sports in China. Conclusions 1. The college sports talent development model is the inevitable way for Chinese sports and should be viewed as the important mission of Chinese sports development. 2. Because of changes in political, social, and economical systems, the development of Chinese collegiate sports is unbalanced at this period. 3. The decline in the development of Chinese collegiate sports can be attributed to: 1) lack of funding, 2) inappropriate coaching education and training, 3) poor organization of high level competitions, 4) lack of high quality of research, and 5) lack of rules for college enrollment.